2018
DOI: 10.1007/s12663-018-1126-z
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of 5-Fluorouracil and Curcumin Nanohybrid Formulations for Improved Chemotherapy Against Oral Squamous Cell Carcinoma

Abstract: Purpose The chemotherapeutics agent, 5-fluorouracil (5-FU), and curcumin (Cur), a natural antioxidant, has a wide pharmacological window to treat oral carcinoma; however, both drugs have limited bioavailability. This research study designs to develop a nanoemulsions (NEs) formulation by combining 5-FU and Cur to improve anticancer activity against oral cavity squamous cell carcinoma (OSCC) cells from the diversified origin for in vitro analysis, SCC090 (human tongue) and SCC152 (human hypo-pharynx). Methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Nanoemulsions provide targeted delivery and sustained-release that are of importance in promoting anti-cancer activity of both curcumin and 5-fluorouracil. [288] These studies are in agreement with the capability of nanoparticles as synergistic factors in anti-cancer therapy. Table 2 summarizes the recent progress in using nanoaprticles for therapy against oral cancer.…”
Section: Oral Cancersupporting
confidence: 79%
“…Nanoemulsions provide targeted delivery and sustained-release that are of importance in promoting anti-cancer activity of both curcumin and 5-fluorouracil. [288] These studies are in agreement with the capability of nanoparticles as synergistic factors in anti-cancer therapy. Table 2 summarizes the recent progress in using nanoaprticles for therapy against oral cancer.…”
Section: Oral Cancersupporting
confidence: 79%
“…37−39 It is now a wellaccepted fact that the nanoparticles were absorbed at the surface of the cancer cells and eventually got internalized into the cell and through various mechanisms caused cell death. 39 But due to lack of targeted delivery, normal cells are affected too. Hybrid nanoparticles have proven to be advantageous over other strategies due to their targeted and controlled delivery against cancers.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although recent studies have reported the advancement of combination therapy to eradicate oral cancer, the morbidity and mortality rates are not changing. It is now a well-accepted fact that the nanoparticles were absorbed at the surface of the cancer cells and eventually got internalized into the cell and through various mechanisms caused cell death . But due to lack of targeted delivery, normal cells are affected too.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nowadays, it is likely that there are other options for chemotherapy. For example, 5-fluoro-uracil, cisplatin, carboplatin, paclitaxel and docetaxel are among the chemotherapy drugs most often used for oral and oropharyngeal cancers; these may be used alone or combined with other drugs 42,43…”
Section: Discussionmentioning
confidence: 99%